Examining the Role of Green Infrastructure as an Advocate for Regeneration - Mell, Ian (Frontiers in Sustainable Cities, 2022)
The alignment of Green Infrastructure (GI) planning principles with urban regeneration mandates can have a significant impact on the long-term socio-economic and ecological functionality of an area. As a mechanism to address landscape dereliction GI has been promoted as offering a suite of options to revitalise denuded spaces. This can take many forms including tree planting, waterfront redevelopment, the regeneration of former industrial sites, and a rethinking of spaces to make them more ecologically diverse. However, the successes seen in GI-led regeneration need to be considered in terms of the geographical, political, and socio-economic context. The following provides a review of regeneration projects that have integrated GI into development principles, examining whether these have led to positive change. Through a reflection on the scale, focus and location of these projects we discuss the factors that have shaped investment before identifying key factors that influence the inclusion of GI in regeneration works. The paper concludes that we have a growing catalogue of projects that can be used as a ‘green print’ to align GI with regeneration to successfully delivery landscape rehabilitation and socio-economic revitalisation.